2007
DOI: 10.1108/02656710710774719
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance as a critical element for driving excellence in corporate social responsibility

Abstract: PurposeThe purpose of this paper is to enhance understanding of corporate governance (CG) in delivering excellence in corporate social responsibility (CSR).Design/methodology/approachThe paper demonstrates models of CG and the associated elements affecting CSR. It addresses the integration of CSR into management systems through a framework as a process‐based management system and studies the role of leadership style for socially responsible organizations. The paper develops a comprehensive questionnaire that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 20 publications
1
70
0
6
Order By: Relevance
“…The need for further research on the integration of corporate sustainability approaches with core business processes has been emphasized (Asif et al, 2011). In addition, scholars have often suggested the importance of such approaches being implemented into every level of an organization if they are to have a meaningful impact (Castka et al, 2004;Shahin and Zairi, 2007;Zadek, 2007). Second, the reviewed articles concluded that an IMS is beneficial for practitioners based on the commonalities found in the QMS and EMS standards.…”
Section: Discussionmentioning
confidence: 99%
“…The need for further research on the integration of corporate sustainability approaches with core business processes has been emphasized (Asif et al, 2011). In addition, scholars have often suggested the importance of such approaches being implemented into every level of an organization if they are to have a meaningful impact (Castka et al, 2004;Shahin and Zairi, 2007;Zadek, 2007). Second, the reviewed articles concluded that an IMS is beneficial for practitioners based on the commonalities found in the QMS and EMS standards.…”
Section: Discussionmentioning
confidence: 99%
“…One of the possible explanations for this gap can be found in the inadequate abilities of major decision makers and boards of directors in particular who drive companies' CSR achievements(D. A. Carter, Simkins, & Simpson, 2003;Hazlett et al, 2007). In line with the underlying CSR concept, boards of directors are collectively accountable to a broad range of stakeholder groups.…”
Section: Introductionmentioning
confidence: 94%
“…CSR can be defined as the broader responsibility towards society of an organisation. In addition to the economic evaluations, both researchers and practitioners recognise the value of additional measures of corporate success (Carroll, 2000;Hazlett, McAdam, Sohal, Shahin, & Zairi, 2007;Jamali, Safieddine, & Rabbath, 2008). Corporations are "no longer expected to be mere contributors to the global economy, but rather to reconcile and skillfully balance multiple bottom lines and manage the interests of multiple stakeholders" (Jamali, 2008) Despite the growing research interest in the topic of CSR, organisational performance in this domain is still found to be limited.…”
Section: Introductionmentioning
confidence: 99%
“…Verslo subjektai yra atsakingi ne tik už pelningą prekių ir paslaugų gamybą -tarp verslo ir visuomenės egzistuoja socialinis susitarimas (žr. Blowfield, Frynas, 2005;Pirsch et al, 2007;Shahin, Zairi, 2007). 2.…”
Section: įMonių Socialinės Atsakomybės Teorinės Nuostatosunclassified